A survey on active magnetic attitude control algorithms for small satellites - Ovchinnikov, M. Yu; Roldugin, D.S. (Progress in aerospace sciences, 2019)
Control algorithms for the active magnetic attitude control systems are covered in the survey. Three different situations in the magnetic system implementation are considered. First, angular velocity damping is covered. Second part is devoted to the combined operation of the active magnetic system with other actuators and with the help of some passive stabilization concepts. Magnetic control torque is restricted in its direction, as it cannot be implemented along the geomagnetic induction vector. This restriction may be lifted by enhancing the active magnetic attitude control with other actuators and concepts. This comes at the cost of restrictions on the available attitude modes of the satellites. Namely, passive gravity-gradient stabilization provides the nadir pointing; bias momentum satellites are restricted by the wheel axis pointing along the orbital normal; spin stabilized satellites acquire only one axis attitude. Finally, solely three-axis magnetic attitude control is considered. Different approaches to the control torque restriction problem are covered, with distinction between the local feedback laws and optimization methods. The survey does not cover passive magnetic control concepts and auxiliary role in the reaction wheels momentum unload. Comparison of the covered algorithms is provided to highlight the authors’ opinion on the algorithms modern implementation and further research directions.